Avaliação histopatológica de lesões por queimaduras de 3°grau em ratos Wistar com e sem diabetes, tratados com o laser de baixa potência - Mendonça, Diego Eterno de Oliveira (2014)
The use of low level lasers in the burning wounds healing has been described in the literature with a great variety of treatment parameters such as multiplicity of wave lenghts, energetic dosages and time of use. Objective: the aim of this study was to compare the effect of low potency AsGaAl laser in the third degree burning wounds healing in Wistar rats with and without diabets. Methodology: this project was approved by the ethics committee in Animals use from UFG, protocol number 007/2012.100. The animals were distributed into 4 groups: a) control group non diabetic; b) treated group non diabetic; c) diabetic control group; d) diabetic treated group. The treated groups received an energetic dosage of 3 J/cm2 in the first 7 days and 6 J/cm2 after the seventh experimental day. The animals received changes of the occlusive bandages embedded with silver sulphadiazine and all of them were accompanied throughout 3, 7, 14, 21 and 30 days for the macroscopic, morphometric and microscopic aspects evaluation. The parametric "t test" was used for the statistical analysis. Results: the comparison of the wounds from the diabetics and non diabetics animals showed that the treatment with low laser induced a significant reduction (p<0.05) of the contraction area; macroscopically there were no differences between groups. Regarding the microscopic findings there was a significant increase in angiogenesis (p<0.05) and increase in the fibrin presence (p<0.05) when compared the treated groups from diabetic and non diabetic animals in 3rd and 14th days of experiment. In the treated diabetic animals the angiogenesis in the 14th day and the number of fibroblasts in the 14th and 21st days of experiment presented a significant difference (p<0.05) when compared to the non treated group. Also there was greater collagen disposition throughout the 14th, 21st and 30th days of experiment in all treated groups when compared to the control groups. In conclusion the low laser treatment reduced the injury in long term, stimulating the angiogenesis, fibrin deposition, fibroblasts and collagen deposition.